Managing cognitive load in information literacy instruction - Hostetler, Kirsten; Luo, Tian (Educational technology research and development, 2021)
This study examined how instructional librarians can incorporate principles from cognitive load theory to engage students in research and improve learning outcomes for a common library instructional delivery model. The study employed a between-subjects, quasi-experimental design to compare how instructional sessions would impact information literacy competency and response time, using a dual-task measurement of cognitive load. The results of this study indicated there are limited gains in competency following instruction via this delivery model and participants disengaged from the primary task, indicating a need for future research into motivational design when cognitive capacity is strained.